2019
DOI: 10.1001/jamadermatol.2019.2724
|View full text |Cite
|
Sign up to set email alerts
|

Natural Does Not Mean Safe—The Dirt on Clean Beauty Products

Abstract: Clean beauty, also known as natural skin care, is having a moment. From 2017 to 2018, the natural skin care market grew by 23% to 1.6 billion dollars, accounting for over 25% of the 5.6 billion dollars of annual skin care sales in 2018. 1 Staunch warnings from influencers such as Gwyneth Paltrow, whose blog Goop warns readers "Do you want antifreeze (propylene glycol) in your moisturizer? We're going to guess no," 2 have ignited fear in consumers who are now hungry for skincare that is safe and nontoxic. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 13 publications
(25 reference statements)
0
32
0
Order By: Relevance
“…Finally, it is interesting that consumers prioritized "natural" ingredients. However, the term "natural" has not been defined by the FDA, making it more of a marketing term than a true indication of a product's components [25].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is interesting that consumers prioritized "natural" ingredients. However, the term "natural" has not been defined by the FDA, making it more of a marketing term than a true indication of a product's components [25].…”
Section: Discussionmentioning
confidence: 99%
“…In reality, parabens, as preservatives, help prevent microbial infections and are among the preservatives with the lowest rates of allergic reactions [40] and no studies have shown any direct link between parabens and any health problems [41]. These preservatives have also helped prevent potential severe health issues such as the Pseudomonasinduced corneal ulcers reported in the 1970s due to an inadequately preserved mascara [12]. Increasing frequency of internet searches for "health" and "natural" compared to "effective".…”
Section: Misconceptions About the Meaning Of Chemical And Natural In mentioning
confidence: 99%
“…Its success is undeterred by the safety issues that plagued prominent natural products such as Jessica Alba's baby wipes and baby powder, which were recalled in 2018 because of mold and contamination by microorganisms [11]. The success of "natural" and "clean" cosmetics is also unaffected by the fact that these claims are not regulated [11] and from the evidence that cosmetic ingredients described as natural are not necessarily safer [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Without rewriting this very short Editorial, I would like to echo the sentiments of Drs Rubin and Brod. 1 If, in fact, the US Food and Drug Administration does not have definitions for “clean” and “natural,” the terms “clean beauty” and “natural skin care” are open to very broad interpretation (and misinterpretation). And this has consequences.…”
mentioning
confidence: 99%